2023
DOI: 10.1097/mnm.0000000000001663
|View full text |Cite
|
Sign up to set email alerts
|

The roles of 68Ga-PSMA PET/CT and 18F-FDG PET/CT imaging in patients with triple-negative breast cancer and the association of tissue PSMA and claudin 1, 4, and 7 levels with PET findings

Abstract: Aim Aim of study is to compare the results of Gallium-68-prostate-specific membrane antigen ( 68 Ga-PSMA) and 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography(PET)/computed tomography (CT), to evaluate the correlation between PET findings and the level of PSMA, Claudin (Clau) 1, 4, and 7 receptors obtained by immunohistochemical (IHC) analysis, and to determine potential predictive and prognostic values in TNBC.Methods Forty-seven lesions of 42 subjects diagnosed TNBC both underwent PET/CT scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Few studies have reported the results of PET/CT with radiolabeled PSMA ligands in breast cancer patients [12,[16][17][18][19], most of which were single-case presentations. Two larger studies are of special interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported the results of PET/CT with radiolabeled PSMA ligands in breast cancer patients [12,[16][17][18][19], most of which were single-case presentations. Two larger studies are of special interest.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed PSMA positivity in 76% of primary breast cancer tumors and 90% of metastatic lesions in all breast cancer subtypes, although PSMA scans exhibited a lower detection rate than [ 18 F]FDG in the analyzed group. Arslan et al presented a comparison between PSMA immunohistochemical expression and PSMA radiotracer uptake in breast cancer, which indicated a positive and similar level [17]. Bertagna et al presented a systematic review, which included 11 case studies evaluating radiolabeled PSMA PET/CT in breast cancer; all of them were 68 Ga-PSMA imaging [18].…”
Section: Discussionmentioning
confidence: 99%
“…The overall sensitivity and specificity were, respectively, 99.2% and 93.6% for [ 18 F]FDG vs. 84% and 91.8% for [ 68 Ga]Ga-PSMA-11, respectively, with similar accuracy ([ 18 F]FDG AUC 0.86-0.95; [ 68 Ga]Ga-PSMA-11 AUC 0.74-0.94). Another study by Arslan et al [24] prospectively reported the results of forty-two TPN BC who underwent both [ 68 Ga]Ga-PSMA-11 and [ 18 F]FDG (thirty-six staging and six recurrent patients). A total of 46 of the 47 primary lesions were FDG avid (mean SUV max 22.2 ± 15.2), whereas 38 of 47 showed PSMA expression (mean SUV max 6.6 ± 3.4).…”
Section: Breast Cancermentioning
confidence: 99%
“…In this context, the possible application of PSMA in the detection of brain metastases should also be considered [23,28,31]. Further data are needed to assess the potential role of PSMA PET in BC patients, which may provide a novel therapeutic vascular target in patients with negative receptor status [23][24][25]. Unclear applications of PSMA-PET include TC, where it may be useful in selected patients with either [ 131 I]I-negative or [ 18 F]FDG-negative tumor lesions [26,28].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%